Pirólise rápida da cianobactéria Spirulina para produção de combustíveis e químicos - Chagas, Bruna Maria Emerenciano das (2016)
Recently microalgae and cyanobacteria have been widely studied as a source of biofuels due to its high yield, high oil content and ability to grow on a wide variety of climates and land without competing with food production. Pyrolysis is an effective thermochemical conversion method capable of converting biomass to fuels, including bio-oil, bio-char and gas. Bio-oil is a liquid mixture of organic compounds that can be a source of valuable chemicals and potential to replace diesel oil depending on its quality. It has been shown that bio-oil from microalgae and other proteinaceous biomass are more stable, have a low oxygen content and higher calorific value than those produced from lignocellulosic feedstock, though contains high nitrogen content due to the presence of protein in its constitution. Spirulina is a cyanobacteria that has been studied in the thermal degradation processes due to its high protein and low lipids content. In this thesis, we investigated the potential for production of fuels and chemicals from the fast pyrolysis of Spirulina. Conventional fast pyrolysis experiments in Py-GC/MS were performed to investigate the influence of pyrolysis parameters such as temperature, heating rate and residence time in distribution of products. The pyrolysis yield was maximized at 450 °C and 30 s, regardless of heating rate. H-ZSM5 (23) showed the maximum hydrocarbon yield and the largest phenols reduction when compared to the other zeolites, but the total nitrogenated compounds were not significantly reduced by any catalyst tested although some specific nitrogenous have been reduced or eliminated. H-β (38) was also able to increase aromatics production, although its effect was less significant when compared to H-ZSM5 (23) and (50). Subsequently tests of Spirulina fast pyrolysis were conducted in USDA’s bubbling fluidized bed pyrolysis reactor under different reaction atmospheres. Conventional (N2 atmosphere) and reactive (Tail Gas Reactive Pyrolysis - TGRP) pyrolysis were tested. Biooil, bio-char and gas obtained from TGRP process had their fuel characteristics improved when compared to the products from conventional pyrolysis. TGRP Spirulina pyrolysis oil showed an increased concentration of aromatics hydrocarbon and the presence of nitrogenous compounds with single nitrogen atom (pyridines, pyrroles, indoles, nitriles and amides), low oxygen content and low acidity being thermally stable therefore a good feedstock for distillation process. Distillation successfully allowed concentrating various chemicals into distillate fractions which, in turn, could be individually isolated for processing to fuels or chemical co-products.